Extracellular Matrix Roles During Cardiac Repair - Jourdan-LeSaux, Claude (2010)
The cardiac extracellular matrix (ECM) provides a platform for cells to maintain structure and function, which in turn maintains tissue function. In response to injury, the ECM undergoes remodeling that involves synthesis, incorporation, and degradation of matrix proteins, with the net outcome determined by the balance of these processes. The major goals of this review are a) to serve as an initial resource for students and investigators new to the cardiac ECM remodeling field, and b) to highlight a few of the key exciting avenues and methodologies that have recently been explored. While we focus on cardiac injury and responses of the left ventricle (LV), the mechanisms reviewed here have pathways in common with other wound healing models.